Faktor-Faktor yang Mempengaruhi Laju Pertumbuhan Penduduk di Kecamatan Bawen Kabupaten Semarang Tahun 2000-2015 - Nasichah, Almaulida Dianatun; Saptono, Putro; Puji, Hardati (Geo-Image, 2018)
This research was aims to know what factors that affect the rater of growth the population in Bawen. The method is used descriptive guantitative approach and qualitative and linier regression to know how much impact multiple factor of birth, death and migration in affect the level of the population rate. Data collection techniques that is the primary data obtained from a guestronnaire and interview, while the secondary data obtained from the data related agencies, documents and library research. The result showed that population growth that the areas of research from 2000-2015 included in the high category due to increased each year the growth of 0,40%. The factors that most affect the growth rate of the population is factors migration sign in, it is known from figure migration entry increased by the number of migrant because the availability of jobs. The infulence of factors birth of the population growth amounting 2,59% and the influence of factor death of the population growth amounting 10,63% also mean that population growth factors also influence the rate of growth the population. Factor that influence the lowest factors is migration out that the effcet of 0,18%.